Structural fire safety design of square and rectangular tubed-reinforced-concrete columns. (February 2021) - Yang, Dongdong; Liu, Faqi; Huang, Shan-Shan; Yang, Hua
Highlights: Fire performance tests of two rectangular TRC columns were conducted and reported. FEA yielded good predictions for fire performance of TRC columns. Parametric studies on the fire resistance of square and rectangular TRC columns were conducted. A structural fire design method for square & rectangular TRC columns with or without fire protection was proposed. Abstract: The tubed-reinforced-concrete (TRC) columns have gained increasing use in the high-rise buildings and large-span stadiums in China, whereas the structural fire design method for square and rectangular TRC columns is still missing. Finite element analysis of the fire performance of square and rectangular TRC columns was conducted using a sequentially-coupled thermo-stress model. This model yielded good predictions against the experimental results of square TRC columns. Fire tests on two rectangular TRC columns were also conducted and presented in this paper, to further calibrate the model. Parametric studies were then conducted, through which it was found that the fire resistance of square and rectangular TRC columns decreases with the increase of load ratio or slenderness ratio and increases as the sectional dimension enlarges. Sectional aspect ratio has a minor influence on the fire resistance of rectangular TRC columns. A practical design method was proposed, for the first time, to determine the fire resistance of square and rectangular TRC columns with or without fire protection. The buckling reduction coefficient could be determined by the EC3 buckling curve (c) or the JGJ/T471 buckling curve. The heat transfer equations given in the Japanese AIJ recommendation were modified to determine the temperatures of the steel tube and rebars and equations were proposed to determine the equivalent temperatures of the concrete core.